2010
DOI: 10.1111/j.1468-3083.2010.03612.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the STS gene in 40 patients with recessive X‐linked ichthyosis: a high frequency of partial deletions in a Spanish population

Abstract: Amplification of exons 1, 5 and 10 is reliable in screening RXLI in the population studied here. No correlation was found between phenotype and the extent of the deletions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 23 publications
0
12
0
2
Order By: Relevance
“…One more case of partial deletion of STS spanning exons 7‐10 has been recently reported in a boy with primary microcephaly due to co‐occurrence of mutations in the ASPM gene . Different from these occasional observations, an exceptional rate of 25% has been reported in a series of Spanish patients . The authors suggested that this uncommon finding should be explained by the high incidence of consanguineous patients and by a founder effect …”
Section: Discussionmentioning
confidence: 59%
“…One more case of partial deletion of STS spanning exons 7‐10 has been recently reported in a boy with primary microcephaly due to co‐occurrence of mutations in the ASPM gene . Different from these occasional observations, an exceptional rate of 25% has been reported in a series of Spanish patients . The authors suggested that this uncommon finding should be explained by the high incidence of consanguineous patients and by a founder effect …”
Section: Discussionmentioning
confidence: 59%
“…Globally about 90% of XLI patients have complete deletions of the STS gene and flanking sequences, one of the highest ratios of chromosomal deletions among all genetic disorders [16,21,22]. A small number of point mutations with functional implications and partial deletions have also been reported (Human Gene Mutation Database, HGMD; (http://www.hgmd.cf.ac.uk, July 2019) without any evidence of genotype/phenotype correlation [18,23].…”
Section: Discussionmentioning
confidence: 99%
“…X-linked ichthyosis (XLI, OMIM#308100) is a relatively rare hereditary keratinization disorder that affects between 1 in 2000 and 1 in 6000 males worldwide ( 1 ). Patients with XLI typically manifest generalized dryness and scaling of the skin with polygonal, thick dark scales that affect the flexures ( 2 ), whereas the palms and soles are usually spared. XLI is caused by a partial or complete deletion in the steroid sulfatase gene ( STS ), which leads to a deficiency of steroid sulfatase (SSase) activity ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with XLI typically manifest generalized dryness and scaling of the skin with polygonal, thick dark scales that affect the flexures ( 2 ), whereas the palms and soles are usually spared. XLI is caused by a partial or complete deletion in the steroid sulfatase gene ( STS ), which leads to a deficiency of steroid sulfatase (SSase) activity ( 2 ). SSase is a 62 kDa microsomal enzyme that is essential for the hydrolysis of 3β-sulphate esters from cholesterol sulfate (CSO 4 ) ( 3 ) and a range of other sulfated steroid hormones.…”
Section: Introductionmentioning
confidence: 99%